IMPLEMENTATION OF ENVIRONMENTAL EDUCATION IN THE NATURAL SCHOOL CURRICULUM - Nandi Kurniawan; Annisa Salsabilla (Journal Learning Geography, 2022)
Environmental education should be given to children from an early age and ideally given education in the form of direct experience in contact with nature so that direct experience can shape behavior, values, and habits to respect the environment. This study aims to describe the implementation of environmental education in an integrative learning model in natural schools. This research was conducted at the high school of the Indonesian Nature School, Cipedak, South Jakarta. The method used is a qualitative approach. The results of the study show that the Indonesian Natural School implements the integration of environmental education in Project Based Learning with the exemplary method as the first and foremost. With the principles of the Seven Green Principles of SAI, environmental education is part of the moral curriculum as the foundation for other curricula translated in the form of rules, building concepts, to activities that are combined holistically.